Circular RNAs in cancer: roles, mechanisms, and therapeutic potential across colorectal, gastric, liver, and lung carcinomas - Ayushi Malviya; Rajabrata Bhuyan (Discover Oncology)
Abstract The prominence of circular RNAs (circRNAs) has surged in cancer research due to their distinctive properties and impact on cancer development. This review delves into the role of circRNAs in four key cancer types: colorectal cancer (CRC), gastric cancer (GC), liver cancer (HCC), and lung cancer (LUAD). The focus lies on their potential as cancer biomarkers and drug targets. Our study analyses the reported circRNAs in the mentioned malignancies, examining their nature, functions, targets, origins, and contributions as tumor enhancers or suppressors. The approach involved assessing full-text reports on PMC, utilizing keywords such as “CircRNA” and “Cancer types,” coupled with bioinformatics, experimental assays, or clinical investigations. Exclusions encompassed non-English publications, conference abstracts, letters, and expert opinions. The findings unveil 577 identified circRNAs across these cancer types: 124 in CRC, 177 in GC, 93 in HCC, and 183 in LUAD. Mechanistic insights into how circRNAs modulate gene expression in cancer are explored, particularly their interactions with microRNAs and RNA-binding proteins. Dysregulation of circRNAs across various cancers and their potential as diagnostic and prognostic indicators are synthesized. The exploration extends to the potential of targeting circRNAs as a novel cancer therapy strategy, either through inhibiting oncogenic circRNAs or reinstating tumor-suppressive ones. This article discusses the challenges and prospects in harnessing circRNAs for cancer diagnostics and therapies. These comprehensive analyses hold promise for advancing cancer research and fostering the development of innovative therapies and diagnostics.